Assessment of myocardial infarctions knowledge, attitudes and beliefs among adults living in Riyadh Saudi Arabia – insights from cross-sectional study - Wajid Syed; Osama Samarkandi; Abdulmajeed A. Alanazi; Nader Alotaibi; Mahmood Basil A. Al-Rawi (Scientific Reports)
Abstract Globally, the prevalence of coronary artery disease (CAD) is increasing, accounting for a third of all deaths worldwide including myocardial infarctions (MIs) which represent the most severe clinical manifestation of CAD and are among the most dangerous coronary events. Therefore, this study aims to assess the knowledge of symptoms and risk factors of MIs, as well as attitudes and beliefs regarding MIs and confidence in recognizing CAD symptoms in Riyadh, Saudi Arabia. A cross-sectional study was conducted among individuals living in Riyadh, Saudi Arabia between November 2023 and April 2024 to assess their knowledge and beliefs about CAD and MIs. Data collection was done using convenience sampling with pretested and validated questionnaire. Furthermore, recruiting more sample was achieved by distributing the questionnaires using the snowball technique. ANOVA and Student’s t-test were used to determine the association between variables, with a p-value of < 0.05 considered statistically significant. Among respondents, approximately 65.5% were male, 27.3%, fell between the ages of 26 and 30 and 59.1% held a master’s degree. In terms of marital status, the majority, 76.2%, were married. The majority (90%) stated that jaw pain was a symptom of a heart attack, followed by chest pain/pressure (85.9%), weakness/fatigue (85.8%), palpitations/rapid heart rate, and chest discomfort (83.4%). Most respondents (91.6%) were aware that smoking and obesity could increase the risk of MIs, while 85.3% believed that a family history of coronary heart disease could affect the risk of MIs. Additionally, 92.3% said they would seek medical care if they experienced chest pain within 15 min. The respondents’ gender (p = 0.001), age (p = 0.004), education (p = 0.001), and marital status (p = 0.004) were significantly associated with levels of knowledge of MI. The findings showed that half of the study population had good knowledge and were well-informed about jaw and chest pain as the main symptoms of MI. Despite understanding the clinical potential of MI, the majority expressed low confidence in their ability to identify heart attack symptoms and recommended health education about the illness to provide prompt assistance.